ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERTUMBUHAN ASET PERUSAHAAN ASURANSI JIWA DI INDONESIA - Andryano, Ade Fahreza; Fatimah, Atika (Media Mahardhika, 2024)
Life insurance asset growth during the 2018-2022 period fluctuated. The data shows low asset growth in 2018 and 2019, then in 2020 asset growth did not experience growth due to the Covid-19 pandemic. The decline in people's purchasing power and economic uncertainty caused by Covid-19 has led to a decrease in demand for life insurance products. The purpose of this study is to determine the effect of insurance income, investment returns and capital growth on asset growth. This research method uses panel data regression using data from 30 life insurance companies for 5 years, namely 2018 to 2022. The results of this study are that the insurance income variable has a significant effect on the insurance growth variable, the investment return variable has no significant effect on the asset growth variable and the capital growth variable has a negative but significant effect on the asset growth variable. Keyword: Insurance Income, Investment Return, Capital Growth, Asset Growth